INTRAOCULAR PRESSURE CHANGES AFTER ND-YAG LASER CAPSULOTOMY - AWAN, ABDUL AZIZ; KAZMI, SAJID HASSAN; BUKHARI, SYED ASHFAQ (Journal of Ayub Medical College Abbottabad, 2001)
Background: 28-43% of the patients develop posterior capsular thickening after extra capsular cataract surgery. Nd YAG laser capsulotomy is a method of choice to treat this complication. Method: We conducted a prospective, clinical, randomized comparative study to evaluate the post YAG laser IOP rise in 54 patients at Ayub Teaching Hospital Complex. Result: There were 43% male and 57% female patients with a mean age of 63.6 years. The mean time for capsular opacification was 14.6 months. Postoperative visual improvement was 6'24 to 6/6. All patients showed post laser IOP rise that was controlled by Topical Beta-blockers and steroids effectively.